On Finite Dimensional Hilbert Space Frames, Dual and Normalized Frames and Pseudo-inverse of the Frame Operator - Njagi, L.; Nzimbi, B. M.; Moindi, S. K. (Journal of Advance Research in Mathematics and Statistics (ISSN 2208-2409), 2018)
In this research paper we do an introduction to Hilbert space frames. We also discuss various frames in the Hilbert space. A frame is a generalization of a basis. It is useful, for example, in signal processing. It also allows us to expand Hilbert space vectors in terms of a set of other vectors that satisfy a certain condition. This condition guarantees that any vector in the Hilbert space can be reconstructed in a numerically stable way from its frame coe?cients. Our focus will be on frames in ?nite dimensional spaces.